A High-Efficiency Isolated Wide Voltage Range DC-DC Converter Using WBG Devices - Alfredo Medina-Garcia; Juan Cruz-Cozar; Diego P. Morales-Santos; Noel Rodriguez; Manfred Schlenk (IEEE Access, 2022)
The recent release of the standard USB-PD 3.1 specifies variable output voltages from 5 V to 48 V featuring a step forward towards a universal adaptor but rising new challenges for the converter topologies used up to now. In such applications, a first AC-DC stage is followed by a DC-DC stage. In this paper, emerging WBG technologies are applied to the asymmetrical half-bridge flyback topology, demonstrating the potential of such combination as a wide voltage range DC-DC stage. Its suitability for high-density and high-efficiency USB-PD Extended Power Range (EPR) and battery charger applications is discussed. The impact of different switching technologies, silicon and wide band gap, is analyzed. A general method to dimension the converter is presented and an iterative process is used to evaluate the theoretical efficiency under different conditions and switching devices. Finally, the advantages of the presented converter using Gallium Nitride (GaN) devices are demonstrated in a 240 W DC-DC prototype. It achieves a full load efficiency of 98%, and it is able to deliver an output voltage from 5 V to 48 V with input voltage range from 120 V to 420 V, as well an outstanding power density of 112 W/inch3 uncased.